Radical love : an introduction to queer theology - Cheng, Patrick S. (New York : Seabury Books, 2011)
Contextual theologies have developed from a number of perspectives -- including feminist theology, black theology, womanist theology, Latin American liberation theology, and Asian American theology -- and a wide variety of academic and general introductions exist to examine each one. However, Radical Love is the first introductory textbook on the subject of queer theology. In this lucid and compelling introduction, Cheng provides a historical survey of how queer theology has developed from the 1950s to today and then explicates the themes of queer theology using the ecumenical creeds as a general framework. Topics include revelation, God, Trinity, creation, Jesus Christ, atonement, sin, grace, Holy Spirit, church, sacraments, and last things, as seen through the lenses of LGBT theologians. - Publisher.
What is queer theology? -- A genealogy of queer theology -- God : the sending forth of radical love -- Jesus Christ : the recovery of radical love -- Holy spirit : the return to radical love.
Includes bibliographical references (p. 141-154) and index.
Keywords: Queer theology; Homosexuality -- Religious aspects -- Christianity; Homosexuality -- Religious aspects -- Christianity; Queer theology